Faktor-Faktor Yang Berpengaruh Terhadap Motivasi Petani Dalam Pembuatan Pupuk Organik Cair Dari Limbah Tempe - Ucca Anantariya; Ugik Romadi; Harwanto Harwanto (Jurnal Sosial Ekonomi Pertanian, 2023)
Abstract The purpose of this study is to determine the factors that influence the motivation of farmers in making tempeh waste liquid organic fertilizer. This research was conducted in Beji Village, Junrejo District, Batu City, East Java in March-May 2023. Sampling was carried out using the purposive sampling method where from 11 farmer groups 3 farmer groups were selected to be included in the specified criteria with a total of 70 people. Data collection was conducted by interviews and using questionnaires that had been tested for validity and reliability. The data analysis used was multiple linear regression with SPSS 25. The results showed that the factors that influence the motivation of farmers in making liquid organic fertilizer from tempeh waste are age, length of farming, education, profit, and complexity. Land area, cosmopolitanism, and facilities and infrastructure have no real effect on farmers' motivation.